"Estudio del efecto de los aceites de sacha inchi (Plukenetia huyuallabamba), anjojolí (Sesamum indicum), maní (Arachis hipogaea), en la elaboración de salchicha vegetal tipo "Frankurt" - Mendez Viteri (2020)
This research was carried out in order to study the effect of sacha inchi, sesame and peanut oils, extracted by hot and cold pressing, for the production of vegetable sausage type "Frankfurt". To determine physical- chemical yields and characteristics (fatty acid profile, acidity, pH, ash, peroxide index and relative density) in oils, an ANOVA was applied using DBCA according to AxB factorial arrangement and 3 repetitions: Factor A (Oilseeds) and Factor B (Extraction Method). To differentiate treatments, the Tukey significance test (p>0.05) was applied. The results analysis was performed with the Statistica, Statgraphics, and InfoStat statistical packages....................................................